Stenotrophomonas maltophilia in a university hospital of traditional Chinese medicine: molecular epidemiology and antimicrobial resistance. Issue 3 (July 2017) - Zhao, S.; Yang, L.; Liu, H.; Gao, F.
Summary: Stenotrophomona maltophilia has emerged as an important opportunistic pathogen that is highly antibiotic resistant. Analysis of antibiotic susceptibilities, drug-resistant gene profiles and molecular typing of S . maltophilia was undertaken in a university hospital of traditional Chinese medicine in East China. Resistance to sulphamethoxazole (SXT) was found to be an indicator of multi-drug resistance. SXT resistance was mediated by sul and dfrA genes in integrons, especially class 1. Some evidence of clonal dissemination was found, indicating the occurrence of cross-transmission of antibiotic-resistant strains within the hospital. This underscores the need for effective control and prevention measures in hospitals.